2019
DOI: 10.1186/s12896-019-0574-y
|View full text |Cite
|
Sign up to set email alerts
|

LC-MSMS based screening of emerging pollutant degradation by different peroxidases

Abstract: BackgroundThe presence of a wide range of bioactive organic pollutants in wastewater and municipal water sources is raising concerns about their potential effects on humans. Not surprisingly, various approaches are being explored that can efficiently degrade these persistent organic pollutants. Use of peroxidases has recently been recognized as a novel remediation approach that may have potential advantages over conventional degradation techniques. However, testing the abilities of different peroxidases to deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…It is worth highlighting the interesting obervation that roxithromycin, the highest molecular weight (836 g/mol) EP tested in our study, which was completely recalcitrant to all the rDyPs tested, showed around 50% degradation with Pf DyP in the presence of HOBT ( Table 3 ). However, as seen in our current study, the addition of a redox mediating species is not universally beneficial [ 36 ] and some redox mediating species exert no influence on the catalytic efficiency of the enzymes [ 36 , 42 , 43 ]. For example, the degradation of all pollutants by Tc DyP was unaffected when HOBT was added to the system ( Table S1 ).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…It is worth highlighting the interesting obervation that roxithromycin, the highest molecular weight (836 g/mol) EP tested in our study, which was completely recalcitrant to all the rDyPs tested, showed around 50% degradation with Pf DyP in the presence of HOBT ( Table 3 ). However, as seen in our current study, the addition of a redox mediating species is not universally beneficial [ 36 ] and some redox mediating species exert no influence on the catalytic efficiency of the enzymes [ 36 , 42 , 43 ]. For example, the degradation of all pollutants by Tc DyP was unaffected when HOBT was added to the system ( Table S1 ).…”
Section: Resultsmentioning
confidence: 93%
“…We have recently published on the potential use of a bioanalytical approach that can be used to simultaneously test the peroxidase-mediated degradation of a large number of organic pollutants in a mixture. The study has described the use of LCMSMS to develop an MRM method that can simultaneously detect 21 different EPs in solution [ 36 ]. A similar MRM approach was adopted in this study, which was based on using LCMSMS to develop an MRM method for 31 EPs belonging to different chemical classes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations